Direct costs prediction of structural elements of small and medium rise buildings - Ujene, A.O.; Idoro, G.I. (Penerbit UKM, 2015)
The failure of cost anticipation and allocation in construction is attributable to ignorance of the nature and values of elemental direct costs in developing countries. This study aims at providing bases for precise and simplified prediction and management of direct costs of structural building elements for labour-only contracts. The objectives of the study are to identify quantitative variables influencing direct costs of structural building elements and develop cost prediction models for small and medium rise buildings. A total of 216 low and medium rise building projects were used for analyses. Data were obtained from cost records and published data. Tools used for data analyses were descriptive and standard regression analyses. The results show that the six models developed have adjusted R2 ranging between 0.742 and 0.830 indicating high degree of prediction dependability. Of the eleven variables reliably used to predict the direct costs of six structural building elements the gross floor area, bid price and labour prices made the strongest unique contribution to the direct costs. It is recommended that direct costs should be predicted with elemental cost models adopted for simplified project planning, accurate cost prediction, and ease of overhead allocation among low and medium income families who mostly use labour only contract system.